The use of mesenchymal stem cells in the treatment of osteogenesis imperfecta: An integrative and qualitative review of literature (Research, Society and Development, 2025)
Osteogenesis Imperfecta (OI) is a hereditary bone disease that affects children, resulting in extreme bone weakness leading to musculoskeletal deformities and fractures. OI is caused by mutations in the genes that code to produce collagen in bones, a substance essential for the formation and strength of bones. Based on this, the objective of this review is to investigate the role of mesenchymal stem cells in the treatment of osteogenesis imperfecta as well as to investigate innovative therapies in the treatment of the disease. This study is a qualitative and integrative review of the literature carried out through an active search in the Medical Literature Analysis and Retrieve System Online (medline) database, in accordance with the precepts established by the Standards qualitative research guideline. For Reporting Qualitative Research (SRQR). Articles published in full without language restrictions were selected for analysis and inclusion based on the controlled DeCS/MESH descriptors: mesenchymal stem cells and osteogenesis imperfecta through the combination of words with the Boolean descriptors AND and OR in the information sources. It was observed in the study that treatment with mesenchymal stem cells brought hope to patients with osteogenesis imperfecta since pre-clinical studies in animal models and clinical studies demonstrated a reduction in the occurrence of fractures and an improvement in bone density with this type of therapy.